2012
DOI: 10.1088/0004-637x/749/2/136
|View full text |Cite
|
Sign up to set email alerts
|

The FORMATION OF THE Hα LINE IN THE SOLAR CHROMOSPHERE

Abstract: We use state-of-the-art radiation-MHD simulations and 3D non-LTE radiative transfer computations to investigate Hα line formation in the solar chromosphere and apply the results of this investigation to develop the potential of Hα as diagnostic of the chromosphere.We show that one can accurately model Hα line formation assuming statistical equilibrium and complete frequency redistribution provided the computation of the model atmosphere included nonequilibrium ionization of hydrogen, and the Lyman-α and Lyman-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
361
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(379 citation statements)
references
References 43 publications
14
361
4
Order By: Relevance
“…This, however, is in direct contrast with the results of recent numerical simulations which suggested that Hα fibrils are visible manifestations of high-density ridges aligned with the magnetic field (Leenaarts et al 2012), thus serving as an indirect tracer of the vertical-to-horizontal transition of the magnetic field orientation around magnetic flux concentrations. This was addressed by de la Cruz Rodríguez and Socas-Navarro (2011) who compared the observed orientation of fibrils in Ca ii 8542 Å images to the chromospheric magnetic field vector, inferred from observed polarization signals originating from the same spectral line.…”
Section: Indirect Tracing Of Chromospheric Fieldscontrasting
confidence: 91%
“…This, however, is in direct contrast with the results of recent numerical simulations which suggested that Hα fibrils are visible manifestations of high-density ridges aligned with the magnetic field (Leenaarts et al 2012), thus serving as an indirect tracer of the vertical-to-horizontal transition of the magnetic field orientation around magnetic flux concentrations. This was addressed by de la Cruz Rodríguez and Socas-Navarro (2011) who compared the observed orientation of fibrils in Ca ii 8542 Å images to the chromospheric magnetic field vector, inferred from observed polarization signals originating from the same spectral line.…”
Section: Indirect Tracing Of Chromospheric Fieldscontrasting
confidence: 91%
“…A similar kinematic analysis performed on the He ii distance-time maps shows similar values of acceleration and speed with respect to Hα. This suggests that the upper chromosphere and the transition region respond similarly to the increase of pressure or density produced by the arrival of the coronal shock which leads to emission enhancements (Vršnak and Cliver, 2008;Leenaarts, Carlsson, and Rouppe van der Voort, 2012;Krause et al, 2015).…”
Section: About the Kinematics Of The Wave Eventmentioning
confidence: 96%
“…The 3D case remains prohibitive . Leenaarts et al (2012Leenaarts et al ( , 2015 therefore restricted their numerical 3D Hα formation studies to a single simulation snapshot.…”
Section: Introductionmentioning
confidence: 99%